Ethics of Scientific Writing and Publication in Higher Education: A Qualitative Analysis - Dea Febriana; Isni Khoiria; Rabiyah Ritonga; Fatimah Hasibuan; Taufik Taufik; Aulia Rahmat; Nurdalilah Nurdalilah (International Journal of Community Service (IJCS), 2026)
This qualitative research examines the implementation of ethics in scientific writing and publication practices in higher education institutions to strengthen academic integrity and improve the quality of scholarly publications among university students. Involving 50 students, 4 lecturers, 3 journal reviewers, and 2 academic administrators from the Faculty of Indonesian Language and Literature Education at Universitas Graha Nusantara, the study employed mixed qualitative methods including structured observations (8 academic writing sessions), semi-structured interviews (9 participants), focus group discussions (2 sessions with 30 students), document analysis, plagiarism screening reports, and student reflective journals over a four-month period. Data were analyzed using thematic analysis with open and axial coding procedures to identify patterns in students’ understanding of academic ethics, publication responsibility, and scientific writing practices. Results revealed significant improvements in students’ academic writing ethics across six dimensions: citation and referencing skills (8-student increase to Proficient level), plagiarism awareness (12-student increase), ethical use of research sources (10-student increase), scientific argumentation (Advanced category achievement), publication responsibility (38 students in Advanced category), and academic integrity commitment (5-student progression to Highly Proficient level). Thematic analysis identified six primary themes: increased awareness of academic honesty (24 occurrences), improved scientific writing quality (28 occurrences), responsible publication practices (31 occurrences), ethical challenges in digital academic environments (26 occurrences), collaborative academic supervision (29 occurrences), and implementation barriers in academic writing culture (17 occurrences). The study demonstrates that strengthening ethics education in scientific writing and publication effectively develops students’ academic responsibility while fostering integrity, professionalism, and credibility in higher education environments.